Multicenter Prospective Analysis of Hypertrophic Olivary Degeneration Following Infratentorial Stroke (HOD-IS): Evaluation of Disease Epidemiology, Clinical Presentation, and MR-Imaging Aspects - Schaller-Paule, Martin A.; Steidl, Eike; Shrestha, Manoj; Deichmann, Ralf; Steinmetz, Helmuth; Seiler, Alexander; Lapa, Sriramya; Steiner, Thorsten; Thonke, Sven; Weidauer, Stefan; Konczalla, Juergen; Hattingen, Elke; et al. (Frontiers in Neurology, 2021)
Introduction: Ischemic and hemorrhagic strokes in the brainstem and cerebellum with injury to the functional loop of the Guillain-Mollaret triangle (GMT) can trigger a series of events that result in a secondary trans-synaptic neurodegeneration of the inferior olivary nucleus. In an unknown percentage of patients, this leads to a condition called the hypertrophic olivary degeneration (HOD). Characteristic clinical symptoms of HOD progress slowly over months and consist of a rhythmic palatal tremor, vertical pendular nystagmus and Holmes-tremor of the upper limbs. Diffusion Tensor imaging (DTI) with tractography is promising to identify functional pathway lesions along the cerebello-thalamo-cortical connectivity and to generate a deeper understanding of the HOD pathophysiology. The incidence of HOD development following stroke and timeline of clinical symptoms has not yet been determined in prospective studies - a prerequisite for the surveillance of patients at-risk. Methods and analysis: Patients with ischemic and hemorrhagic strokes in the brainstem and cerebellum with a topo-anatomical relation to the GMT will be recruited within certified stroke-units of the Interdisciplinary Neurovascular Network Rhine-Main. Matching lesions are identified using a predefined MRI-template. Eligible patients are prospectively followed up and present at the Goethe-University Frankfurt Brain Imaging Center at four months and at eight months after the index event. During study-visits, a clinical neurological examination and brain MRI including high resolution T2-, proton-density- weighted imaging and DTI tractography will be performed. Fiberoptic endoscopic evaluation of swallowing is optional if palatal tremor is encountered. Study outcomes: Primary endpoint of this prospective clinical multicenter study is to determine the frequency of radiological HOD development in patients with a posterior fossa stroke affecting the GMT at eight months after the index event. Secondary endpoints are identification of: (1) the timeline and relevance of clinical symptoms, (2) lesion localizations more prone to HOD occurrence, and (3) the best MR-imaging regimen for HOD identification. Additionally, (4) DTI tractography data will be used to analyze individual pathway lesions. The aim is to contribute to the epidemiological and pathophysiological understanding of HOD and hereby facilitate future research on therapeutic and prophylactic measures Clinical Trial Registration: HOD-IS is a registered trial at https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00020549.